النقل السلبي في النصوص المترجمة من الملايوية إلى العربية لدى الدارسين الماليزيين : دراسة وتحليل - Muhammad Hakim Rosly (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Studies on negative transfer with special reference to the analysis of words, phrases and sentences in different error types including morphology, lexicology, syntax and semantics have long been central to researchers. Nevertheless, negative transfer especially in Malay to Arabic translated texts need to be examined due to the lack of special focus in previous studies. Therefore, this study attempts to investigate negative transfer by extensively explaining types and causes of these problems in Malay-Arabic translated texts among Malaysian students. Errors made by these students were examined. Previous studies confined their scope in analyzing negative transfer whether words or phrases or sentences used by Malaysian students. In contrast, this study analyzes negative transfer in Malay to Arabic translated texts among Malaysian students more comprehensively. Thus, the researcher divided them into four linguistic levels: 1) Word and term level, 2) Structure and collocation level, 3) Sentence level, 4) Connective and cohesion level, and including cultural level. The theoretical part of this study discusses the concept of transfer and its types from several perspectives and interests among previous researchers in different fields. The relationship between transfer theory in second language learning and translation was examined. Furthermore, the researcher studies the reality of translation exercises in Arabic Language syllabus and books for secondary level in Malaysia because it is part of writing skills that should be acquired by Malaysian students. The data of this study were collected from 200 various texts translated from Malay to Arabic by 230 Malaysian students of Intensive Arabic Language Course conducted at Kolej Pengajian Islam Johor (MARSAH), Johor Bahru for two academic sessions (2011/2012 and 2012/2013). One of the research findings is that the majority of students preferred and followed the phrase order and sentence formation style of their mother tongue due to negative transfer from the Malay language into their translated texts. The use of some loan words from Arabic led to negative transfer as well.